(untitled) (Journal of Environmental Science and Natural Resources, 2021)
A survey was conducted to assess the status of rooftop and homestead gardening in Sadar upazila of Bogura in Bangladesh. The study revealed that 66% rooftop gardeners and 70% homestead gardeners preferred gardening for production of healthy and fresh food. According the survey there were about 80 type of plants in rooftop gardens and 87 types in homestead gardens. These plants were fruits (97%), vegetables (86%), flowers (64%), spices (72%), medicinal plants (64%), ornamental plants (23%) and plantation crops (12%). The amount of time they had to invest for gardening ranged from only less than half-an-hour to an hour. About 28% homestead gardeners received training on gardening from GOs and NGOs while most of the rooftop gardeners gained knowledge from agro-based television programs. The study revealed that a very few gardeners (18%) considered rooftop gardening for economic benefit while a remarkable number of homestead gardeners (24%) considered gardening for economic return on top of producing fruits and vegetables for family consumption. Finally this study concluded that both rooftop and homestead gardening can be complementary means for increasing the production and consumption of fresh fruits and vegetables and thus can contribute in achieving food security and safety. Environ. Sci. & Natural Resources, 12(1&2): 157-164, 2019